Venoms, venomics, antivenomics - Calvete Chornet, Juan José (2009)
Venoms comprise mixtures of peptides and proteins tailored by Natural Selection to act on vital systems of the prey or victim. Here we review our proteomic protocols for uncoiling the composition, immunological profile, and evolution of snake venoms. Our long-term goal is to gain a deep insight of all viperid venom proteomes. Knowledge of the inter- and intraspecies ontogenetic, individual, and geographic venom variability has applied importance for the design of immunization protocols aimed at producing more effective polyspecific antivenoms. A practical consequence of assessing the cross-reactivity of heterologous antivenoms is the possibility of circumventing the restricted availability of species-specific antivenoms in some regions. Further, the high degree of target specificity makes toxins valuable scaffolds for drug development.